Invalidation Of Administrative Acts And Temporal Modulation Of Their Effects - Clarissa Sampaio Silva; Ivson Antonio de Souza Meireles (Revista de Direito Administrativo e Gestão Pública, 2016)
This study aims to analyze, within the theme of invalidation of administrative acts, the possible temporal modulation effects, which are usually retroactive. The act of declaration of nullity, even within the period established by law, brings in different situations analyzed in the jurisprudence of judicial courts, the Court of Auditors, and also the doctrine, offenses against constitutional principles of public administration, as the reasonableness and proportionality, so that inspired in the modulation of the unconstitutionality of laws declaration, similar solutions can be sought, with increased demands of motivation by the Government.